Conductivity of a 2D electron crystal over liquid helium in the region of coupled electron–ripplon resonances: Physics in Quantum Crystals - Syvokon, Vitaliy; Kovdrya, Yuri (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
The dependence of the coupled electron–ripplon oscillations spectrum of a 2D electron crystal over liquid helium on the holding electric field is studied at a temperature much lower than the temperature of melting. An analysis of the spectrum near the main resonance (0,1) allowed finding both the real and imaginary components of the crystal conductivity. The imaginary part of the conductivity is shown to be in good agreement with theoretical estimates. At the same time, additional theoretical and experimental studies are necessary to clear up the possible reasons for energy losses in the electron crystal.